CSC438 - Fundamental of Data Structure / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2023)
In this course, we attempt to understand the concept of information organization and manipulation in a computer, emphasizing the use of data structure in problem solving. The object-oriented approach will be followed to develop the programming solutions